Effects of Repeated Cisplatin and Monosodium Glutamate on Visceral Sensitivity in Rats - Yolanda López-Tofiño; Laura López-Gómez; Marta Martín-Ruíz; Jose Antonio Uranga; Kulmira Nurgali; Gema Vera; Raquel Abalo (Cells)
Cisplatin, a chemotherapeutic drug, is known for causing gastrointestinal disorders and neuropathic pain, but its impact on visceral sensitivity is unclear. Monosodium glutamate (MSG) has been shown to improve gastrointestinal dysmotility and neuropathic pain induced by cisplatin in rats. This study aimed to determine if repeated cisplatin treatment alters visceral sensitivity and whether dietary MSG can prevent these changes. Male Wistar HAN rats were treated with saline or cisplatin (2 mg/kg/week, ip) for 5 weeks, and visceral sensitivity to intracolonic mechanical stimulation was recorded after the final cisplatin administration (week 5) and one-week post-treatment (week 6). In a second cohort, rats treated with cisplatin or saline also received MSG (4 g/L) in their drinking water, and visceral sensitivity was evaluated on week 6. Finally, the untouched distal colon was obtained from a third cohort of animals one week after treatment to assess immunocyte infiltration. Cisplatin significantly increased colonic mechanical sensitivity on week 6 but not on week 5. MSG did not prevent cisplatin-induced visceral hypersensitivity on week 6 and even exacerbated it. On week 6, compared with the control, cisplatin (with or without MSG) did not modify the colonic infiltration of eosinophils, macrophages, neutrophils, or mast cells. Although MSG seems to be useful in ameliorating some of the adverse effects of cisplatin, such as gastrointestinal motility disturbances or neuropathic pain, it does not alleviate visceral pain.